RECOMMENDATIONS ON SOCIAL SUPPORT TO FAMILIES AFFECTED BY HIV/AIDS - Liakh, Tetiana; Spirina, Tetiana; Alieksieienko, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of this article is to provide recommendations for social workers and social field practitioners of state and non-governmental organizations working with families affected by HIV/AIDS. The article identifies a series of crisis stages of families affected by HIV/AIDS. Families caring for HIV-positive children go through four crisis stages. The first stage comes after the report about an unconfirmed possibility that a child has HIV. The second stage is when the diagnosis confirms the child’s HIV positive status. The third stage coincides with the first signs of opportunistic infections in the child. The fourth stage is associated with the progression of the disease and the development of the fourth clinical stage of HIV infection. At each of these stages, families need medical, psychological, and social support. In line with professional support, an effective method of assistance and a way to overcome a crisis can be self-help groups, in which people learn to voice their difficulties and problems, seek support or provide it to other families. Using the results of the study gained through focus groups with social work practitioners from various regions of Ukraine, the authors developed recommendations on supporting families affected by HIV/AIDS.